Non-collagenous dentin protein binding sites control mineral formation during the biomineralisation process in radicular dentin - Retana-Lobo, Cristina; Guerreiro-Tanomaru, Juliane Maria; Tanomaru-Filho, Mario [UNESP]; de Souza, Beatriz Dulcineia Mendes; Reyes-Carmona, Jessie (MDPI, 2020)
The biomineralisation of radicular dentin involves complex molecular signalling. Providing evidence of protein binding sites for calcium ions and mineral precipitation is essential for a better understanding of the remineralisation process. This study aimed to evaluate the functional relationship of metalloproteinases (MMPs) and non-collagenous proteins (NCPs) with mineral initiation and maturation during the biomineralisation of radicular dentin. A standardized demineralisation procedure was performed to radicular dentin slices. Samples were remineralised in a PBS-bioactive material system for different periods of time. Assessments of ion exchange, Raman analysis, and energy dispersive X-ray analysis (EDAX) with a scanning electron microscope (SEM) were used to evaluate the remineralisation process. Immunohistochemistry and zymography were performed to analyse NCPs and MMPs expression. SEM evaluation showed that the mineral nucleation and growth occurs, exclusively, on the demineralised radicular dentin surface. Raman analysis of remineralised dentin showed intense peaks at 955 and 1063 cm-1, which can be attributed to carbonate apatite formation. Immunohistochemistry of demineralised samples revealed the presence of DMP1-CT, mainly in intratubular dentin, whereas DSPP in intratubular and intertubular dentin. DMP1-CT and DSPP binding sites control carbonate apatite nucleation and maturation guiding the remineralisation of radicular dentin.
Keywords: Bioactive materials; Biomineralisation; Carbonate apatite; Dentin remineralization; Matrix metalloproteinases; Non-collagenous proteins; Radicular dentin